Lost in the sun - Graff, Lisa (Lisa Colleen), 1981- (Philomel Books, an imprint of Penguin Group (USA), 2015)
"As Trent Zimmerman struggles to move past a traumatic event that took place several months earlier, he befriends class outcast Fallon Little, who helps him understand that he can move on"--